Factors affecting delay in diagnosis and treatment of lung cancer - Yeşiler, Fatma İrem; Çimen, Filiz; Atikcan, Şükran (Journal of Surgery and Medicine, 2020)
Aim: Lung cancer (LC) is one of the most prominant causes of mortality in the world. Delays in diagnosis and treatment gravely affect the prognosis of the disease. Our aim is to investigate the factors that affect delay in diagnosis and treatment in patients with LC. Methods: In this retrospective cohort study, LC patients who were diagnosed in the pulmonary diseases clinic between January 2010 and August 2011 were retrospectively evaluated from patient files. The sociodemographic characteristics of the patients (age, gender, occupation and educational level), symptom type, presence of other malignancies, radiological location of the lesion, diagnostic method, histological type, presence of endobronchial lesion, stage of LC, length of times between admission, diagnosis and treatment were noted. Results: One hundred seven (87.7%) patients were male and 15 patients (12.3%) were female. Eighty-nine patients (73%) were under the age of 70 years. Ninety-eight patients were diagnosed with non-small cell (NSCLC) and 24 patients, with small cell lung cancer (SCLC). The mean duration from symptom onset to admission to the hospital (SA), from symptom onset to pathological diagnosis (SP), from symptom onset to initiating treatment (ST), from admission to the hospital until pathological diagnosis (AP), from admission to the hospital until initiating treatment (AT) were 30, 60, 75,5, 14, 33 days, respectively. There were statistically significant differences between SP, AP, AT periods (P=0.017, P=0.011 and P=0.006 respectively) with regards to education levels, and between SA, SP, ST, and from symptom onset to performing an initial radiological examination (SR) periods in terms of social security institution (P<0.05 for all). AT time of patients with SCLC was shorter than that of patients with NSCLC. Conclusion: Early diagnosis of LC is particularly important. Therefore, determination of factors affecting the delay in diagnosis and treatment of LC, probable causes, and solutions should be investigated.